2018
DOI: 10.9734/ajrcs/2018/40255
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Neem, Garlic and Aloe Extracts in the Management of Postharvest Potato Soft Rot Caused by Erwinia carotovora

Abstract: Potato (Solanum tuberosum L.) production in Kenya is limited by soil borne diseases especially soft rot bacteria caused by Erwinia carotovora. Although the use of synthetic pesticides has significantly contributed in the management of E. carotovora, their use is often associated with environmental pollution and loss of beneficial soil biodiversity. Here, we investigated the efficacy of neem (Azadirachta indica M.), garlic (Allium sativum M.) and aloe (Aloe secundiflora Engl.) extracts, on the development of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Researchers have speculated that Chinese chives can also inhibit the occurrence of soft rot. Further studies have shown that extracts of Chinese chives plants can significantly reduce decay from bacterial soft rot resulting from infection by Erwinia carotovora (Ndivo et al, 2018 ) or Pectobacterium carotovorum (Simeon and Abubakar, 2014 ). Moreover, rotation of Chinese chives with other crops affects crop soil microbial quantity, species, community structure, and diversity (Gu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have speculated that Chinese chives can also inhibit the occurrence of soft rot. Further studies have shown that extracts of Chinese chives plants can significantly reduce decay from bacterial soft rot resulting from infection by Erwinia carotovora (Ndivo et al, 2018 ) or Pectobacterium carotovorum (Simeon and Abubakar, 2014 ). Moreover, rotation of Chinese chives with other crops affects crop soil microbial quantity, species, community structure, and diversity (Gu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%